2018
DOI: 10.1002/pmic.201800075
|View full text |Cite
|
Sign up to set email alerts
|

Porins and Amyloids are Coded by Similar Sequence Motifs

Abstract: The relationship between amino acid sequences of the β‐hairpin structures and amyloidogenic β‐arcade‐forming motifs are of special interest because, similar to amyloid fibrils, most of the β‐hairpin repeat (BHR) structures have the so‐called cross‐β arrangement. Moreover, β‐hairpin is considered as a probable intermediate structure in amyloidogenesis. In this work, a bioinformatics sequence analysis of the known BHR structures is performed in search of amylodogenic motifs able to form β‐arcade fibrils. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Among many other interesting observations, this analysis revealed that the BHRs of porins share high level of sequence similarity with β‐arcade motifs. This finding provided a mechanistic explanation for the ability of some amyloidogenic sequence to fold in either the ring‐like shape oligomers or elongated amyloid fibrils …”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Among many other interesting observations, this analysis revealed that the BHRs of porins share high level of sequence similarity with β‐arcade motifs. This finding provided a mechanistic explanation for the ability of some amyloidogenic sequence to fold in either the ring‐like shape oligomers or elongated amyloid fibrils …”
mentioning
confidence: 82%
“…[14] Based on the premises that many β-hairpin repeat (BHR) structures have cross-β arrangement typically found in amyloid fibrils, Villain et al analyzed the relationship between the amino acid sequences of the β-hairpin structures and amyloidogenic βarcade-forming motifs. [16] To this end, they conducted a comprehensive bioinformatics analysis of BHR structures in order to find if they contain amylodogenic motifs able to form β-arcade fibrils. [16] Among many other interesting observations, this analysis revealed that the BHRs of porins share high level of sequence similarity with β-arcade motifs.…”
Section: Doi: 101002/pmic201900085mentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a possibility that it could be widespread. Bioinformatic analysis suggested that the porin fragments forming the inner part of the pore were capable of forming amyloid structures [194].…”
Section: Aggregation Prone Porins and Enzymesmentioning
confidence: 99%